Korespondencja Praskiej Izby Apelacyjnej z miastami na Śląsku w latach 1548–1740 - Daniel Wojtucki (Klio, 2012)
Prague Appeal Chamber (niem. Appellationsgericht, czes. Apelačni soud) was brought into being by an instruction of Ferdinand I in January 1548. Since that year, everyone who was not satisfied with a verdict of a town council or court, which verdicts were not decisive since then, from any royal town could appeal to Prague Appeal Chamber through town council. It dealt mainly with civil and criminal cases or advised in lawsuits. It may suggest, that from Silesian town courts there were mostly sent documents of cases concerning those matters. As it was defined, to Prague Appeal Chamber there were directed cases regarded as important, difficult or dubious. However, it occurred that Prague Court received to consider cases which today would be recognized as highly controversial or even beyond belief. Prague Appeal Chamber also dealt with reviews of privileges possessed by towns (chiefly concerning judiciary matters). Such reviews, for example, took place in 1709 and 1722. Preserved archive records of “Prague Appeal Chamber” were created on the basis of correspondence between judiciary institutions in centers of the Bohemian Crown. That is why they constitute highly valuable material for researchers of judiciary history of these lands, not excluding here Silesia and Lusatia (to 1635).